Prediction of shoulder pain in youth competitive swimmers: The development and internal validation of a prognostic prediction Model - Feijen, S.; Struyf, T.; Kuppens, K.; Tate, A.; Struyf, F. (The American Journal of Sports Medicine, 2021)
Background: Knowledge of predictors for shoulder pain in swimmers can assist professionals working with the athlete in developing optimal prevention strategies. However, study methodology and limited available data have constrained a comprehensive understanding of which factors cause shoulder pain.